The Development of Fashion in Jambi During the Dutch Rule (1906-1942) - Wahyuni, Anny; Fito Dermawan; Muhammad Adi Saputra (Arkus, 2023)
During the Dutch rule period from 1906 to 1942, Jambi experienced significant changes in the fashion sector, which reflected Dutch colonial influence as well as internal changes in Jambi society. The people of Jambi, who had access to colonial culture, began to adopt clothing styles that were considered more modern and luxurious. However, over time, the influence of Dutch fashion began to spread to wider layers of society. This study aimed to explore the development of fashion in Jambi during the Dutch East Indies government (1906-1942). This study is carried out through four steps, namely collecting historical sources, interviewing historical sources, interpreting data, and historiography. Changes in the lifestyle of the people of Jambi during the Dutch rule have influenced the development of fashion and dress styles. Clothing style is not only a visual appearance but also a symbol of social status and identity.